The Relationship between Status and Happiness: Evidence from the Caste System in Rural India - Bert van Landeghem; Anneleen Vandeplas (Institute of Labor Economics (IZA), 2017)
A large number of empirical studies have investigated the link between social status and happiness, yet in observational data identification challenges remain severe. This study exploits the fact that in India people are assigned a caste from birth. Two identical surveys of household heads (each with N=1000) in rural Punjab and Andhra Pradesh show an increasing pattern in economic welfare across the hierarchy of castes. This illustrates that at least in rural regions, one's caste is still an important determinant for opportunities in life. Subsequently, we find that the castes at the top are clearly more satisfied than the lower and middle castes. This result, which is in line with predictions of all major social comparison theories, is robust across the two case studies. The pattern across low and middle castes, however, is less clear, reflecting the complex theoretical relationship between being of middle rank on the one hand, and behaviour, aspirations and well-being on the other hand. In the Punjab sample, we even find a significant U-shape, the middle castes being the least happy. Interestingly, these patterns resemble those found for Olympic Medalists (first documented by Medvec et al. 1995).
Keywords: I31; C1; O12; 330; subjective well-being; happiness; social status; social comparison